A publicly verifiable network coding scheme with null-space HMAC. (2018) - Chen, Yonghui; Zhang, Cheng; Li, Wei; Chen, Tingsong; Zhang, Mingwu
The encode-and-forward mechanism of network coding (NC) system, not only could provide increased network throughput, but also might get seriously vulnerable to pollution attacks. It has been an interesting and challenging topic how to design a secure, efficient and publicly verifiable homomorphic NC scheme. The existing cryptography-based NC schemes are grouped in either public key cryptosystem (PKC), or symmetric key cryptosystem (SKC). NC schemes in PKC naturally have public verifiability, but imply much more computation cost and longer operation delay. NC schemes in SKC have cheaper computations cost, but are dilemma about how to share the secret key to those intermediate nodes who might be malicious. Therefore, in this paper, we provide a new NC scheme that based on null-space HMAC with hierarchically sharing keys. The inner sharing keys are for the destination nodes to verify the integrity of the messages; the outer sharing keys are for the intermediate nodes to verify the integrity of the received packets. Our scheme shows a way how to balance the computation efficiency and the public verifiability for the NC system with a SKC scheme.